Teacher-Question Strategies in EFL Classroom Interaction - Nuryanti; Sari, Ravila; Fauzi, Iwan (Pusat Kajian Bahasa Daerah & Budaya, 2024)
This study aims to analyze the teacher's questioning strategy in English lessons. It was conducted in classroom interaction between teacher and students of SMP Negeri 1 Mentaya Hilir Selatan, in Central Kalimantan Province. The subject of this study was an English teacher and 25 eighth grade of junior high school students. This research used a qualitative approach. Two main data collection instruments were used observation and interview. Through observation, the researcher carefully analyzed the types of teachers questioning strategies during English learning activities. In interview, researcher gain deeper insights from the teacher related with the questioning strategies used by her during teaching. The result revealed that teachers used four questioning strategies in classroom interaction, namely redirection questions, prompting questions, probing questions, and granting waiting time. Then, the result showed the prompting question strategy was the most dominant question strategy, but the teacher was still ineffective in using this strategy because the questions asked still contained many grammatical errors because the teacher sometimes used a mixture of English and Indonesian which caused students only answer briefly. This study implies that the implementation of questioning strategies by the teacher actually has the potential to increase students' activeness in learning English.